Performance of Corrosion Inhibitors Blend for Simulated Industrial Cooling Waters under Dynamic Conditions - Slaiman, Qasim J.M.; Al-Khasab, Abeer A. (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
The inhibitive action of a blend of sodium nitrite/sodium hexametaphosphate (SN+SHMP) on corrosion of carbon steel in simulated cooling water systems (CWS) has been investigated by weight loss and electrochemical polarization technique. The effect of temperature, velocity, and salts concentrations on corrosion of carbon steel were studied in the absence and presence of mixed inhibiting blend. Also the effect of inhibitors blend concentrations (SN+SHMP), temperatures, and rotational velocity, i.e., Reynolds number (Re) on corrosion rate of carbon steel were investigated using Second-order Rotatable Design (Box-Wilson Design) in performing weight loss and corrosion potential approach. Electrochemical polarization measurements were used to study the behavior of carbon steel in different salts concentrations of (CWS) with pH = 7.5 in absence and presence of the inhibiting blend. The results show that the regression model (Box-Wilson Design) that has been developed using experimental data was used to verify that the interaction term of temperature with inhibitors blend and the square term of inhibitors blend are significant for corrosion rate in 0.05 N NaCl solution while the main variables are not pronounced. Also, it is found that the corrosion rate of carbon steel is increased with increasing temperature, rotational velocity, and NaCl salts concentration in uninhibited and inhibited solutions. Inhibition performance of NaNO2+ Na(PO3)6 was found to increase with its concentration up to 800 ppm inhibitors blend, and the corrosion potential is shifted to more positive direction with increasing rotational velocity, and inhibitor blend concentration.